Dampak Kualitas Pelayanan dan Harga Terhadap Minat Berkunjung Kembali Melalui Kepuasan Pelanggan - Yulianti, Ni Kadek Ayu; Sugianingrat, Ida Ayu Putu Widani (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Return visits made by customers are a form of loyalty shown by consumers. This will be very helpful in improving business development in the future. The purpose of this research is to find out how the influence of service quality and price on interest in revisiting through customer satisfaction at the Eva Beauty Salon in Tegallalang Gianyar. The total population is 1,859 people who are all visitors throughout 2021 and the number of samples is 95 people who are obtained by the Slovin formula and will be selected by the purposive sampling method. The test will be carried out using the path analysis method and also the Sobel test. The results found are that directly or indirectly, the quality of service and also the price is able to have a positive and also significant influence on interest in revisiting through papal mediation. It is suggested that companies can improve satisfaction, service quality, and price adjustments to increase consumer interest in visiting again.